Impacto técnico, económico y evaluación experimental de la mezcla asfáltica con adición de caucho y plástico reciclado - García Davila, Richard Michael (2024)
In this research work, the traditional asphalt mixture was modified with the implementation of recycled material, improving some of the mechanical properties of the asphalt, so as to encourage the reuse of commonly consumed materials. Therefore, the research was carried out with a quantitative approach, an explanatory and explorative research scope. Briquettes of conventional asphalt and modified asphalt with recycled plastic and rubber were made in order to analyze their technical properties and performance........